Las Trayectorias Educativas como categoría analítica. Aportes desde el campo de la Sociología de la Educación - Kaplan, Carina Viviana (2022)
This article aims to enrich the analytical study of Educational Paths from recovering from the Sociology of Education contributions from the Structural Genetic approaches of Pierre Bourdieu and the Figurative Sociology of Norbert Elías. Understanding that this category is fundamental to know the educational inequality and the challenges of a historical time that requires the expansion of horizons of symbolic opportunities for the social sectors most affected by the consequences of wild capitalism, recover from both approaches, three conceptions: 1 Reality must be understood in a double objective and subjective dimension; 2. Both dimensions of the real are expressed in the practical sense that underlies the implementation of Social Reproduction Strategies; and 3. Social reality must be understood in its genesis, reconstructing the struggles that have given rise to it. Recovering from these approaches these conceptions, will allow to deepen the investigation on the conceptions of time, performance and subject that underlie the analytical study of the Educational Paths, complicating the knowledge of other temporalities, routes and subjects, own of social, historical and relational processes.